Les enseignants du premier et du second degré : des identités professionnelles toujours distinctes ? - Virginie Volf (Les éditions de la Maison des sciences de l'Homme, 2018)
Recent developments in the French school system (Loi pour la refondation de l'école, July 2013) bear witness to an institutional will to bring the primary and the middle school close together, and to transcend the historical cleavage that characterize the first degree as the "school of the people" and the second degree as the "schools for the elite". But what will that do to avoid these antagonisms and move towards the same educational culture and professional identity? To address this issue, meetings between primary and middle teachers have been observed. Observations demonstrate that primary and middle school teachers still build on the historical legacy of the school system: in primary schools, pedagogy and consideration for pupils prevail while, in middle schools, subject-specific knowledge is the priority. The article shed light on how middle school actors get the upper hand on the réseau école-collège through the organization of the meetings and the control of the exchanges. They appear as the ones who define the rules. Thus, instead of bringing them together, these meetings between primary and middle schools teachers consolidate the way they perceive each other.